Chaetone G, a new dibenzo[b, e]oxepinone from the insect pathogenic fungus Aschersonia luteola BCC 31749. Issue 3 (20th January 2016) - Kornsakulkarn, Jittra; Saepua, Siriporn; Laksanacharoen, Pattiyaa; Rachtawee, Pranee; Thongpanchang, Chawanee
Graphical abstract: Abstract: Chaetone G (1 ), a new dibenzo[ b, e ]oxepinone, along with the known derivative2, 5α, 8α-epidioxy-(22 E, 24 R )-ergosta-6, 22-dien-3β-ol, and zeorin were isolated from the insect pathogenic fungus, Aschersonia luteola BCC 31749. The structure of1 was elucidated based on the analysis of NMR spectroscopy and mass spectrometry. 5α, 8α-Epidioxy-(22 E, 24 R )-ergosta-6, 22-dien-3β-ol exhibited antibacterial activity against Bacillus cereus with IC50 3.3 μg/mL and also showed cytotoxicity toward NCI-H187 and Vero cells.